The 2018 Recruitment and Selection of Civil Servants In Indonesia: Problems and Solutions - Ismiati Nur Istiqomah; Atika Indah Nur Atsarina (Indonesian Association for Public Administration (IAPA), 2019)
Recruitment and selection of civil servant is an effort of the Government of Indonesia to get a competent civil servants. The 2018 recruitment and selection of civil servant process was using merit system that is conducted online. But in its implementation, there are still many problems found at the Ministries / Institutions and Regional Government levels. This article discusses the issues in the 2018 recruitment and selection of civil servant process, and how ideally the process is supposed to be carried out. The method used in this article is literature review, both from journal articles, news articles, and other data that support research. The findings of the study show that the implementation of the 2018 recruitment and selection of civil servant still leaves some problems. But in this article, authors focuses on problems that are not getting much attention from many parties, such as the lack of attention from government to the needs of employees with future potential, and the subjectivity of the selectors in the interview process. The researcher recommends that the government needs to apply the concept of future potential skills in recruiting prospective civil servants and blind interviews to recruit a competent candidates. This article has limitations because it only uses literature review methods so it is necessary to do an actual research in order to produce research that is closer to the actual reality.